Black Rice Bran Extracts and Fractions Containing Cyanidin 3-glucoside and Peonidin 3-glucoside Induce Apoptosis in Human Cervical Cancer Cells - Rarastoeti Pratiwi; Woro Anindito Sri Tunjung; R. Rumiyati; Alfi Rizqi Amalia (Universitas Gadjah Mada, 2015)
Anthocyanin of pigmented rice inhibits the growth of cancer cells. The cytotoxicity and apoptosisinducing properties of local black rice (cv Cempo Ireng) extracts and fractions, which contain anthocyaninincluding cyanidin 3-glucoside and peonidin 3-glucoside, on human cervical cancer cell line (HeLa cells) hasbeen evaluated. The pigmented rice bran was extracted and fractionated using methanol-HCl. The MTT testwas performed on HeLa cell cultures to observe the IC50 value. Preparative TLC was performed to obtain thefractions of black rice bran. Cyanidin 3-glucoside and peonidin 3-glucoside were identified in the pigmentedrice bran extract and fractions using UHPLC. Flowcytometry analysis was performed to measure the percentageof apoptotic cells. Our results suggest that the fractions are more toxic than the methanolic crude extract withIC50 values of 85.95 ± 5.56 μg/mL (the lowest one) and 408.13 ± 51.9 μg/mL, respectively. The concentration ofcyanidin 3-glucoside and peonidin 3-glucoside in the methanolic extract were 1.89 and 0.84 μg/mg, respectively.The apoptosis induction by fractions F2 and F4 (52 and 55%) were significantly higher compared to fractionF3 and F5 (30 and 33%) and doxorubicin (21%). Cyanidin 3-glucoside was detected in F4 (0.14 μg/ml) whilepeonidin 3-glucoside in F2 (0.012 μg/ml), however both were not detected in F3 and F5.